The Effect Of Canva-Based Flash Card Media On Mathematics Learning Outcomes Of Grade 3 Elementary School Data Building Material - Salsha Ramadhan; Mimin Ninawati (Didaktika: Jurnal Kependidikan, 2024)
Research on the Effect of Canva-Based Flash Card Meida on Mathematics Learning Outcomes on Flat Buildings Material for Grade 3 Students of SDN 05 Pagi Pademangan Timur aims to determine whether or not there is an effect of Flash Card media on Mathematics learning outcomes. The method that research uses is Quantitative. This study has a target research subject from the lower grade, namely grade 3, this research was conducted at one of the schools in Pademangan, by taking a research sample with a final number of 26 samples. The validators filled out a questionnaire in the form of questions and students took the pre-test and post-test data collected through questioning. The validation results indicate that the Canva-based Flash Card media is valid at 71.7% with an N-Gain value of 71.55% in the pre-test and post-test comparison. The hypothesis test shows a significant difference in improving students' metacognitive abilities between the pre-test and post-test results before using Canva-based Flash Card media and the post-test results. The use of Canva-based Flash Card media can be interpreted that it is quite effective in improving the quality of learning Mathematics Flat Buildings material, showing important value in improving the quality of learning.